The Effect of Multimedia As a Means of Delivering Information and Promotion Towards Flashcard Products - Budi, Hutomo Setia; Faustina, Jesslyn (Universitas Ciputra, 2017)
Every product which launched would definitely need a promotion to introduce its products to the society. In the promotion itself, there are various strategies and media to support product promotion. Multimedia is one of the media promotion which is widely used to help in providing information towards products. Flashcards is one of the edugame products which serves to sharpen children’s ability in various aspects such as motoric, visual, and verbal, and encourage children to be more proactive. Besides, flashcards can also become medium for the parents to be more involved and interact with their children. In the product